2015
DOI: 10.1111/eff.12264
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic characteristics of early life history stages of native marble trout (Salmo marmoratus) and introduced brown trout (Salmo trutta) and their hybrids in the Soča River

Abstract: Metabolic potential and respiration rate have been measured in the early life stages of native marble trout Salmo marmoratus (MT), introduced brown trout Salmo trutta (BT) and their hybrids (MH = female of MT 9 male of BT and BH = female of BT 9 male of MT) to examine the differences in their metabolic characteristics. Metabolic potential and respiration rate were lowest in each developmental stage in MT, followed by MH, BT and BH. The ratio between metabolic potential and respiration rate (ETS/R) in larvae wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…Subsequent molecular studies confirmed the presence of hybridization between these two species in the wild ( Giuffra, Guyomard & Forneris, 1996 ; Lucarda et al, 2000 ; Zerunian, 2003 ; Jug, Berrebi & Snoj, 2005 ; Turin, Zanetti & Bilò, 2006 ; Lucarda, 2007 ; Meldgaard et al, 2007 ; Meraner et al, 2010 ; Meraner & Gandolfi, 2018 ). It is still unclear whether these hybrids are adaptively advantaged or disadvantaged (positive or negative heterosis, respectively) either in sympatry or allopatry with ‘genetically pure’ marble trout, though possible ecological differences and interactions between genetically discriminated hybrids and ‘pure’ individuals have been explored ( Meldgaard et al, 2007 ; Meraner et al, 2010 ; Simčič, Jesenšek & Brancelj, 2017 ). Several ecological studies, including some early investigations on population density, size-age structure, and fishing pressure, phenotypically discriminated between pure and hybrid individuals within populations, analyzing them separately ( Alessio et al, 1990 ; Jelli & Duchi, 1990 ; Jelli, Alessio & Duchi, 1996 ; Turin, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent molecular studies confirmed the presence of hybridization between these two species in the wild ( Giuffra, Guyomard & Forneris, 1996 ; Lucarda et al, 2000 ; Zerunian, 2003 ; Jug, Berrebi & Snoj, 2005 ; Turin, Zanetti & Bilò, 2006 ; Lucarda, 2007 ; Meldgaard et al, 2007 ; Meraner et al, 2010 ; Meraner & Gandolfi, 2018 ). It is still unclear whether these hybrids are adaptively advantaged or disadvantaged (positive or negative heterosis, respectively) either in sympatry or allopatry with ‘genetically pure’ marble trout, though possible ecological differences and interactions between genetically discriminated hybrids and ‘pure’ individuals have been explored ( Meldgaard et al, 2007 ; Meraner et al, 2010 ; Simčič, Jesenšek & Brancelj, 2017 ). Several ecological studies, including some early investigations on population density, size-age structure, and fishing pressure, phenotypically discriminated between pure and hybrid individuals within populations, analyzing them separately ( Alessio et al, 1990 ; Jelli & Duchi, 1990 ; Jelli, Alessio & Duchi, 1996 ; Turin, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complex III assays can use tetrazolium dye (reduced to formazan) as the final electron acceptor in place of oxygen. As such, the assay estimates the rate that could be achieved by an organism's energy production pathways by detecting electron transfer activity (Maldonado et al, 2012; Relaxans 1996; Simčič et al, 2017). Initially used to estimate respiration rates in mesopelagic fishes considered too fragile for laboratory acclimation postcollection (Belcher et al, 2020), Complex III activity can estimate potential respiration rate in fishes, estimate growth, and quantify metabolic effects of introgression (Ikeda, 1989; Simčič et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the assay estimates the rate that could be achieved by an organism's energy production pathways by detecting electron transfer activity (Maldonado et al, 2012; Relaxans 1996; Simčič et al, 2017). Initially used to estimate respiration rates in mesopelagic fishes considered too fragile for laboratory acclimation postcollection (Belcher et al, 2020), Complex III activity can estimate potential respiration rate in fishes, estimate growth, and quantify metabolic effects of introgression (Ikeda, 1989; Simčič et al, 2017). By quantifying enzyme Complex III activity at various temperatures, thermal performance curves can be generated for this complex activity in the electron transport system, which can then be used to quantify temperature effects on an organism's metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, seasonal variations in metabolic activity were reported for zooplankton (Simčič and Brancelj 2004) and reptiles (Seebacher et al 2003); metabolic properties of amphipod species were modified when inhabiting contrasting environments, i.e. subterranean vs surface ; metabolic characteristics of freshwater fish were related to their habitat conditions (Simčič et al 2017); and metabolic activity of invasive and native bivalve species differed between two species that varied in competitive ability (Bielen et al 2016). Moreover, many studies exploring metabolic performance or activity indicate the importance of the acclimation of physiological traits to environmental conditions (Pörtner andKnust 2007, Žagar et al 2015a).…”
Section: Introductionmentioning
confidence: 99%